Beneficial shift of rhizosphere soil nutrients and metabolites under a sugarcane/peanut intercropping system - Tang, Xiumei; He, Yonglin; Zhang, Zheng; Wu, Haining; He, Liangqiong; Jiang, Jing; Meng, Weiwei; Huang, Zhipeng; Xiong, Faqian; Liu, Jing; Zhong, Ruichun; Han, Zhuqiang; et al. (Frontiers in Plant Science, 2022)
Intercropping systems have been studied as a sustainable agricultural planting pattern to increase soil quality and crop yields. However, the effects of intercropping systems on root and rhizosphere soil metabolites, and their relationships with soil physicochemical properties, remain poorly understood. Thus, we determined and analyzed the soil physicochemical properties, rhizosphere soil and root metabolites of peanut and sugarcane under different planting patterns. The results showed that pH and the contents of total phosphorus (P), total potassium (K), available nitrogen (N), available phosphorus (P), and available potassium (K) were higher in rhizosphere soil of intercropping peanut than in monoculture peanut, and the content of total P was higher in rhizosphere soil of intercropping sugarcane than in monoculture sugarcane. In addition, sugarcane/peanut intercropping also significantly increased the activities of acid phosphatase and urease in rhizosphere soil. The metabolomics results showed that 32 metabolites, mainly organic acids and their derivatives (25.00%), nucleotides and their metabolites (18.75%), were detected in root and rhizosphere soil samples of peanut and sugarcane. In the MP-S (rhizosphere soil of monoculture peanut) vs. IP-S (rhizosphere soil of intercropping peanut) comparison, 47 differential metabolites (42 upregulated) were screened, including glycerolipids (19.15%), organic acids and their derivatives (17.89%), and amino acids and their metabolites (12.77%). In the MS-S (rhizosphere soil of monoculture sugarcane) vs. IS-S (rhizosphere soil of intercropping sugarcane) comparison, 51 differential metabolites (26 upregulated) were screened, including heterocyclic compounds (15.69%), glycerolipids (11.76%), and organic acids and their derivatives (9.80%). The metabolite species from MP-S, MS-S, IP-S, and IS-S were similar, but some metabolite contents were significantly different, such as adenine, adenosine, maltotriose, thermozeaxanthin-13 and PE-NMe (20:0/24:0). Adenine and adenosine were detected in root and rhizosphere soils, and their levels were increased in the intercropping treatment, which were mainly related to enhanced purine metabolism in root and rhizosphere soils under the sugarcane/peanut intercropping system. Importantly, adenine and adenosine were significantly positively correlated with total P and total K contents, acid phosphatase and urease activities, and pH. This study clarified that the sugarcane/peanut intercropping system could improve soil nutrients and enzymes and was related to purine metabolism.